MODERN BUILDING MATERIALS FOR FLOOR STRUCTURES - Abdullayev Ikromjon Aminjanovich; Toʻlqinov Iqboljon Maxamad ugli; Sotvoldiyev Azamatjon Akramjon ugli (Journals Park Publishing, 2024)
The service life of the floor depends on the covering material. The surface layer of the floor is directly exposed to the operational impact, so it is very important to choose the right type of final covering. The surface covering of the floor can be made from almost all construction materials (wood, polymers, ceramics, natural stone, concrete, metals, etc.). In this article, we will consider several types of modern flooring materials, their advantages and disadvantages.